Factors Associated with Success of Treatment among New Smear Positive Pulmonary Tuberculosis Patients, Phuket Province, Thailand - เสริมแก้ว, ธนิศ; สว่างพันธุ์, กุสุมา (Journal of Health Science of Thailand, 2022)
This research was a retrospective study with the objective to identify the factors associated with success of treatment among new smear-positive pulmonary tuberculosis patients in Phuket Province, Thailand. The population were the patients who were diagnose as new smear positive pulmonary tuberculosis that registered for a treatment from public and private hospitals in Phuket during October 2015 to September 2020. There were 2,094 patients whose data were collected from recorded database. The data were analyzed using descriptive statistics, Chi-square test and multiple logistic regression. The study found that new smear positive pulmonary tuberculosis patients had 84.7% of treatment success rate in fiscal year 2016 – 2020. Patients aged 25-30 years and over 50 years were 3.99 times (95%CI=2.17–7.35) and 1.79 times (95%CI=1.35–2.38) more likely to have treatment success than those younger than 25 years, respectively. Patients with pre-treatment weight of 40 kgs or more were 0.49 times more likely to be successful than those who weigh less than 40 kgs (95%CI=0.32–0.76). Patients with comorbid disease had a chance of successful treatment 4.29 times more likely for those without co-morbidity (95%CI=3.28– 5.60). Patients who were foreign workers with health insurance had a better chance of treatment success than those with universal health insurance scheme [3.30 times (95%CI=1.40–7.75)]. Finally, patients with bacterial density of 3-plus or greater at initiation of treatment were 0.55 times more likely to succeed in treatment than those with lower bacterial intensity (95%CI=0.40–0.76).